EFEK TRANSFER CAIRAN RUMEN KAMBING KE RUMEN DOMBA TERHADAP KUALITAS HASIL KARKAS DOMBA LOKAL - Padang, Padang (AgriSains, 2005)
This study was carried out at the Animal House of Animal Production Faculty, University of Padjadjaran, from 21st March to 8th May 2003.  The objective of the research was to investigate the effects of transferring the rumen liquid of goat on the ram's carcass cuality and pelvic and kidney fat percentation. The number of experimental animal used were 14 lambs with a mean age of ± 10 months and body weight range of between 13.5 and 17.0 kg.            The animals were placed in a big animal house with tile roof, wooden floor, and wooden/wire wall.  The big animal house was then divided into 14 pens with an individual size of               1.0 x 0.75m in each of which was confined an experimental animal. The diet of the animals during the experimental period was field grass having contents of 21.83% dry matter, 12.25% crude protein, and 30.25% crude fibre. The grass was offered ad libitum without concentrate addition. Data collected were analysed with t test with two treatments: DK = control rams and               DP = treatment rams (goat's rumen fluid as much as 50% of rumen wight). The results of study showed that rumen fluid transfer increased (P<0.05) the recipients carcass quality and             the pelvic and kidney fat percentation. Key words : Rumen fluid transfer, carcass cuality, pelvic and kidney.